Design of PLC Based Control System for Rotary Flexible Fixture with PID Compensator - Adi Susanto; Sampurno; Suhardjono (Institut Teknologi Sepuluh Nopember, 2018)
Machining process consist of machine tool, cutting tool and work piece that must securely held by jig and fixture. A rotary flexible fixture prototype then developed, to locate work piece at desired angular position using rotary and tilt angular positioning components to complement machining processes such as CNC mill, EDM, machining center, etc. This research focused on designing PLC based control system with PID compensator for the prototype, this paper however deal with rotary component in particular. Preliminarily, all components assembled into closed-loop transfer function and calculated its frequency domain overall transfer function. Analysis of control system stability then followed, using such methods as Routh-Hurwitz, Nyquist and Root Locus. Next, the system’s time responses need to be evaluated, design targets are rise time less than 0.2 second, settling time not exceeding 0.4 second and zero steady state error with ±2% allowable error. If target are not satisfied, then use of PID compensator. Stability analysis results shows the system are stable according to Routh-Hurwitz, Root Locus, and Nyquist criteria. Time responses analysis results in rise time 0.267 second and settling time 0,476 second. While, the system yield zero steady state error. To meet design targets, PID compensator were employed, after tuning at proportional gain value 1.5, rotary component reached rise time 0,178 second, settling time 0,317 second, well within design target. These results are essential for PLC programming, assembly process and general consideration or recommendation for selecting components to gain a simple yet better perform control system.